2020
DOI: 10.1021/acs.energyfuels.0c00202
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Deoxidization of Lignin and Its Impact on Liquid Products from Pyrolysis

Abstract: In this study, low temperature deoxidization of lignin at temperature range of 200~390°C as a pretreatment method had been exploited to gain high quality pyrolysis products. A two-dimensional infrared correlation spectroscopy (2D-PCIS) was used to analyze the evolution of the functional groups of lignin in the process of low temperature deoxidization, and the deoxidized samples were pyrolysed in the pyrolysis gas chromatography mass spectrometry (Py-GC/MS). The results of 2D-PCIS showed that the decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Mei et al investigated lignin pyrolysis in the temperature range of 200–400 °C. They found that the lignin decomposition reaction accelerated at temperatures greater than 320 °C and that the aromatization reaction intensified at 350 °C.…”
Section: D-pcis Studies Of Biomass Pyrolysis Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mei et al investigated lignin pyrolysis in the temperature range of 200–400 °C. They found that the lignin decomposition reaction accelerated at temperatures greater than 320 °C and that the aromatization reaction intensified at 350 °C.…”
Section: D-pcis Studies Of Biomass Pyrolysis Mechanismsmentioning
confidence: 99%
“…As the pyrolysis temperature increases, a larger number of hydrogen bonds are converted to free −OH groups. 100 Mei et al 122 investigated lignin pyrolysis in the temperature range of 200−400 °C. They found that the lignin decomposition reaction accelerated at temperatures greater than 320 °C and that the aromatization reaction intensified at 350 °C.…”
Section: D-pcis Studies Of Biomass Pyrolysismentioning
confidence: 99%
“…The peaks at 1223 and 1076 cm –1 are the stretching vibration absorption peaks of the C–O and C–O–C bonds of the anhydride ring . The peaks at 1496 and 1600 cm –1 were assigned to the vibration absorption peaks of the benzene ring skeleton . In the FTIR spectrum of PDBMA, the typical characteristic peaks (1850 and 1778 cm –1 ) of anhydride disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…27 The peaks at 1496 and 1600 cm −1 were assigned to the vibration absorption peaks of the benzene ring skeleton. 28 In the FTIR spectrum of PDBMA, the typical characteristic peaks (1850 and 1778 cm −1 ) of anhydride disappeared. The peak at 1715 cm −1 is due to the C�O stretching vibration.…”
Section: Characterization By Fourier Transform Infrared (Ftir) X-ray ...mentioning
confidence: 97%
“…To date, researchers have developed many methods for chemoselective HDO of oxygen-containing molecules, such as alcohols, aldehydes, ketones, amides and nitrogencontaining compounds. [21][22][23] Among them, alcohols are widely used as versatile precursors for the production of other organic molecules in the chemical industry. The selective HDO of alcohols is one of the most fundamental transformations in organic chemistry and plays a crucial role in the total synthesis of complex natural products bearing multifunctional groups.…”
Section: Introductionmentioning
confidence: 99%